Improving Outcomes of Mothers With Opioid Use Disorder Using a Community Collaborative Model. (October 2021) - Jones, Carolyn; Duea, Stephanie; Griggs, Kellie; Johnstone, William; Kinsey, Debbie
Context: Increasing rates of Opioid Use Disorder among pregnant women are a significant public health issue. Care for these women is fragmented, and multiple barriers to care have been identified. Program: The Tides, Inc. is attempting to address these needs by providing comprehensive, coordinated care, beginning in pregnancy and extending beyond the birth of their infant. Implementation: Using a collaborative model, care is coordinated between multiple existing agencies in an effort to reduce barriers and improve access to care. Funding for these services is provided through county funding and existing payor sources (eg, insurance, Medicaid). Evaluation: Participant and program outcomes were evaluated at the end of each year of the program. In addition, participants who had completed the program at the end of year 1 were asked to complete a survey providing qualitative information about their experience in the program. Of these participants, 73% reported no opiate use and 100% had full custody of their infants. Discussion: The Tides, Inc. program utilizes existing resources to provide coordinated and comprehensive care for pregnant women with Opioid Use Disorder. In addition to improving outcomes for women and their infants, this program can reduce cost and burden on community entities such as the justice system and foster care networks. This program can serve as a model for other communities to coordinate care for women and their infants.